Teaching Grammar in Iraqi Secondary Schools by Using the Communicative Approach - Mohamed Ramadhan HASHIM (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
The aim of the present paper is to describe the teaching grammar process in Iraqi secondary schools based on the Communicative Approach (CA) with reference to teacher’s experience and the difficulties that the teachers face during teaching the class. Teaching grammar in Iraqi secondary schools is the dominant content in the syllabus and is preferred to other skills. Additionally, teaching grammar in Iraqi secondary schools using other methods, such as: Grammar-Translation method (GTM) which is considered as the principal method, ‘Direct method’ (DM) and ‘Indirect method’ (IM) enable teachers to meet what learners need during learning the grammatical structures.